PENERAPAN PEMBELAJARAN AKTIF INOVATIF KREATIF EFEKTIF DAN MENYENANGKAN (PAIKEM) MELALUI PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP N 7 KERINCI - Al Ikhlas (Ensiklopedia of Journal, 2019)
Based on observations in SMP N 7 Kerinci that teachers in the process of learning is menoton, students fasif, lack of interest of students to innovate so that learning is not effective. PAIKEM very important in the study of materials mathematic. Besides, the poor performance of students in learning science, it can be seen from the mastery learning students who only reached 38% and the value of many students are under the KKM, it is necessary pengunakan For better learning using study material PAIKEM in Mathematic. This research is a classroom action research (PTK), which consists of several cycles, At each cycle ends with the evaluation. Each cycle consists of planning, implementation, evaluation and reflection. Achievement data obtained using test and student activity using observation sheet. Analysis of data on the activities of students in PAIKEM through a scientific approach to the pre-cycle, the first cycle, second cycle and third cycle has been successful. Analysis of the average student mastery of positive activity on pre-cycle reached 57.78%, in the first cycle reaches 70.10%, 80.08% reached the second cycle and the third cycle analysis reached 84.78%. Based on the percentage of the third cycle can be said that the fifth grade students of SMP N 7 Kerinci district has achieved mastery learning classical. The result showed that the adoption of the model PAIKEM through a scientific approach can increase the activity and student achievement Class VIII SMP N 7 Kerinci district. Based on these results suggested to teachers, especially mathematic teachers that learning model application PAIKEM through scientific approaches developed as an innovation in teaching and learning.